Upregulation of angiotensin-(1–7) formation in human podocytes – enzyme activity assay upon fluid flow shear stress - Debora Kaiser-Graf; Oliver Domenig; Marko Poglitsch; Reinhold Kreutz; Juliane Bolbrinker (PLoS ONE, 2026)
The renin-angiotensin system is known for its role in renal physiology by regulating renal hemodynamics and natriuresis. Overactivation of this system exerts pathological effects in the kidney, primarily mediated by its main effector peptide angiotensin II. Deleterious angiotensin II-mediated effects are counter-regulated at least partly by the biologically active renin-angiotensin system component angiotensin-(1–7). The processing of angiotensin II to angiotensin-(1–7) by prolylcarboxypeptidase, angiotensin converting enzyme 2, and prolyl endopeptidase is cell- and species-specific, with limited knowledge regarding its conversion in human podocytes under conditions of glomerular hyperfiltration. Since hyperfiltration plays a critical mechanistic role in albuminuria progression and chronic kidney disease, understanding the mechanisms underlying podocyte damage due to glomerular hyperfiltration is essential. Therefore, we investigated the conversion of angiotensin II to angiotensin-(1–7) in cultured human podocytes exposed to fluid flow shear stress and subsequently incubated with spiked angiotensin II. Mass spectrometry of cell lysates and supernatants was performed to evaluate the formation of angiotensin-(1–7). Contribution of the respective enzymes to angiotensin-(1–7) formation was assessed using selective inhibitors of prolylcarboxypeptidase, angiotensin converting enzyme 2, and prolyl endopeptidase. We detected increased angiotensin-(1–7) formation upon fluid flow shear stress in podocyte lysates, which was mainly dependent on prolylcarboxypeptidase activity. Our study contributes to a deeper understanding of the intraglomerular processing of angiotensin II towards the alternative renin-angiotensin system and its modulation upon fluid flow shear stress.